WOMEN AND MATRIMONIAL LIVES IN ACEH ‘MATRIFOCAL’ SOCIETY: A PRELIMINARY SURVEY - Srimulyani, Eka (Center for Research and Development of Religious Literature and Heritage, 2015)
Some related marriage traditions, the religious rituals and cultural practices varied across Indonesian societies or ethnic groups. Apart from the principles guided by the Islamic injunctions, the cultural aspects involved in those practices are indeed not typical, modified and changes over the time. In a matrifocal society like Aceh, women had strong roles in adat (cultural) ceremonies such as marriage its related activities as well as ceremonies. This article elaborates some matrimonial tradition within Aceh matrifocal setting of [traditional] Acehenese society. What has changed, and driven behind those changes are among the focus of this brief portrait of women and matrimonial traditions.The data in this article came from my previous research on matrifocality[i], which was then combined with some current data from the field that has connection to the marriage and its wedding practices and ceremonies.[i] Some parts of this research has been published in Al-jamiah Journal of Islamic Studies vol. 48, no. 2, pp. 321 ? 342. Under the title: Islam, Adat and The State: Matrifocality in Aceh Revisited.